“Un-Romanticized” love in Anthony and Cleopatra and The Taming of the Shrew - Arbaayah Ali Termizi, (Penerbit UKM, 2015)
Among Shakespeare’s plays revolving around the theme of love, Anthony and Cleopatra and The Taming of the Shrew develop an un-romanticized attitude by focusing on carnal realities, reinforced through the imagery associated with Cleopatra and Katherine as well as the banquet occasions. In these two plays, the theme of love acquires a carnivalesque approach through which debasement is experienced as a part of love rapports. This paper discusses grotesque representations of love and feasting in the plays by employing relevant viewpoints of the ‘grotesque,’ mainly those theorized by Mikhail Bakhtin. Accordingly, Bakhtinian idea of ‘grotesque realism’ and carnival as well as the concept of degradation related to bodily life are highlighted in their association with carnal realities as portrayed in the selected works. The aim of the study is to demonstrate how the theme of love is un-romanticized through the idea of grotesque. Furthermore, since Bakhtinian analysis targets the comic and regenerative in the grotesque, the elaborate choice of a comedy and a tragedy for this study is assumed to be an illuminating endeavor. Grotesque and its implicative denotation revolve around the concept of language and the discourse carried out by the intention of the characters. The elaboration of linguistic discourse in this study goes along with love ideology in a dramatic text. Thus, Bakhtin's conceptualization of grotesque facilitates the dramatic orientation of love in Anthony and Cleopatra and The Taming of the Shrew, whereby the theme of love gets un-romanticized in these plays.